Inhibitory Effect of Chlorpromazine on RANKL-Induced Osteoclastogenesis in Mouse Bone Marrow Cells - Hiroharu Kawamura; Michitsugu Arai; Akifumi Togari (Elsevier, 2011)
Abstract.: Chlorpromazine (CPZ), the first widely used phenothiazine tranquilizer, is shown to inhibit the action of intracellular calmodulin (CaM) and bone resorption in vivo and in vitro. In this study, CPZ (0.63 - 10 μM) dose-dependently inhibited the formation of tartrate-resistant acid phosphatase (TRAP) staining-positive osteoclast-like cells in mouse bone marrow cells (BMCs) treated with 1α,25(OH)2D3 (10 nM) or soluble receptor activator of nuclear factor-κB ligand (s-RANKL) (20 ng/ml). Expressions of mRNA for the nuclear factor of activated T-cells c1 (NFATc1), a key regulator of osteoclast differentiation; dendritic cell-specific transmembrane protein (DC-STAMP), an essential protein for cell-cell fusion; and characteristic markers of osteoclasts such as TRAP, cathepsin K, carbonic anhydrase II, and calcitonin receptor in BMCs were up-regulated by s-RANKL and decreased by the addition of CPZ (5 μM) or the selective CaM antagonist W7, but not the inactive analog W5. The general CaM kinase (CaMK) inhibitor KN-93 and CaM-dependent phosphatase calcineurin inhibitor FK-506 also inhibited s-RANKL-induced osteoclastogenesis. Phenothiazines such as CPZ, trifluoperazine (TFPZ), and promethazine (PMZ) inhibited s-RANKL-induced osteoclast-like cell formation in mouse BMCs. Osteoclastogenesis inhibitory effects decreased in the order of TFPZ, CPZ, PMZ, depending on their anti-CaM potency. These findings suggest that CPZ inhibits RANKL-induced osteoclastogenesis by its anti-CaM action. Keywords:: chlorpromazine, calmodulin, osteoclastogenesis, bone marrow cell, RANKL